Pengembangan Bahan Ajar Digital Multimodal untuk Materi Trasformasi Energi di Sekolah Dasar - Dwi Galeh Prasetyawan; Erna Retna Safitri; Suratmi Suratmi (Postgraduate, University of Mataram, 2026)
This study aims to design multimodal digital materials on energy transformation in primary education in terms of validity, practicality, and effectiveness in improving students’ conceptual understanding. The study employed design-based research by integrating the Rowntree model for the planning as well as development phases and Tessmer’s formative evaluation (self-evaluation, expert review, one-to-one, small-group, and field test). The subjects of this study consisted of 33 fourth-grade students at SDN 1 Sumber Rezeki. Data were collected through practicality questionnaires, expert validation sheets, and tests, and analyzed using descriptive statistics, paired-sample t-test, and effect size analysis. The validation results showed that the multimodal digital materials were in the highly valid category (94.7%). The practicality test in the one-to-one showed practical category (71%-80%) and small-group evaluation stages fell into the very practical category (86%–92%). The effectiveness test showed a significant increase in learning outcomes, with the mean score improving from 53.42 (pre-test) to 82.90 (post-test) and an N-gain of 0.59 (moderate category) (t = 8.383, p < 0.05), with a Cohen's d effect size of 1.459, which is classified as a large effect.These findings indicated that the developed multimodal digital materials are valid, practical, and effective in improving students' understanding of energy transformation. This study implies that the integration of multimodal elements in digital learning materials can enhance meaningful and contextual science learning. It also serves as an innovative reference for developing instructional materials aligned with 21st-century learning.